Analisis Hukum Penggunaan Dana Wakaf Tunai Untuk Pembangunan Infrastruktur - Faisal Faisal (DE LEGA LATA: JURNAL ILMU HUKUM, 2020)
As a large Muslim population country, Indonesia has great potential one of which is waqf. Waqf can be carried out with movable or immovable objects. Money waqf included in movable objects is often referred to as cash waqf, but it needs to be reviewed legally related to whether or not the results of waqf acquisition are used for infrastructure development in the field of public facilities and social facilities. The research method used in this study is juridical normative. The results showed that under expert opinion, the agreement of some scholars, MUI fatwa, in line with the applicable positive law, through Article 22 letter e of the Law of the Republic of Indonesia Number 41 of 2004 concerning Waqf which was clarified by Article 9 of BWI Regulation Number 4 of 2010 concerning Guidelines for the Management and Development of Endowment Property, that cash waqf funds can be used for infrastructure development including public facilities and also social facilities. However, the need for cash waqf is specifically regulated regarding the mechanism of cash waqf management allocated for infrastructure development so that it has legal certainty and clear management.